Optimization of Diamond Nucleic Acid Dye for quantitative PCR. (October 2016) - Haines, Alicia M.; Tobe, Shanan S.; Linacre, Adrian
Here, we evaluate Diamond Nucleic Acid Dye (DD) for use in quantitative PCR (qPCR) applications. Although DD is a commercially available stain for detection of DNA separated by gel electrophoresis, its use as a detection dye in qPCR has yet to be described. To determine if DD can be used in qPCR, we investigated its inhibitory effects on qPCR at concentrations ranging 0.1–2.5×. Serial dilution of DNA was used to determine the efficiency, sensitivity, and linearity of DD-generated qPCR data in comparison to other commonly used fluorescent dyes such as SYBR Green (SG), EvaGreen (EG), and BRYT Green (BG). DD was found to be comparable with other dyes for qPCR applications, with an R 2 value >0.9 and an efficiency of 0.83. Mitochondrial DNA (mtDNA) target signals were successfully produced by DD over a DNA dilution range of ∼28 ng— 0.28 pg, demonstrating comparable sensitivity to the other dyes investigated. Cq values obtained using DD were lower than those using EG by almost 7 cycles. We conclude that Diamond Nucleic Acid Dye is a cheaper, less toxic alternative for qPCR applications.